Numerical analysis of wave energy converting systems in case of using piezoelectric materials for energy harvesting - Yamac, Halil Ibrahim; Koca, Ahmet (Taylor & Francis Ltd, 2021)
The aim of the study is to model and investigate the wave energy converting system with piezoelectric materials numerically. In this study, computational fluid dynamics software Fluent is used for modelling numerical wave tank. The dynamic mesh technique and volume of fluid method are employed and wave maker is moved by using the user-defined function. Transient Fluent analysis is made to receive values of fluctuating pressures and forces acting on the system. The transient structural module is used to find buckling of plate to use in equation of power. The generated electrical power is calculated from the root mean square (RMS) equation. The RMS value reaches 1.4 W for wave height less than 2 m. The underwater position of the wave harvester, water depth, wave amplitude and period causes the changes in value of the produced electrical energy. If the piezoelectric energy harvester system is positioned close enough to the wave trough formed in the water free surface, it can be accepted as the most efficient system for the same wave parameters. The wave height parameter can be regarded as a more significant and effective variable than the water depth parameter.
Keywords: Simulation; Tank